The Problem of the Stability of the Social System in Ancient Indian Philosophy - V. V. Tuzov; R. R. Mazina (Дискурс)
Introduction. The purpose of the article is to show the effect of the law of correspondence as a factor of stability of the social system and the relevance of this problem for ancient Indian philosophy. The problem of the stability of society was not directly considered in ancient Indian philosophy or in modern literature, especially through the prism of the law of correspondence.Methodology and sources. The work uses content analysis, system approach, dialectics and the concept of self-organization. In addition, the main analysis of the problem of stability in ancient Indian philosophy is carried out on the basis of the law of correspondence between the real relations that connect people at a given moment and the essence of the “social”. This law was formulated and proposed by V.V. Tuzov. The essence of the “social” could be conditionally expressed through the concepts of “equality”, “humanism”, mutual assistance, “justice”. Real relations may deviate from the essence, but by a certain amount, a measure. Going beyond the limits of the measure deprives the system of stability, and it becomes uncontrollable. The main source of analysis is the academic edition of the text Arthashastra (ancient Indian political and economic treatise), as well as “History of political and legal doctrines”, “Development of ideas about management in philosophical thought”.Results and discussion. The article analyzes the ancient Indian philosophical texts to reveal in them, in a latent or explicit form, the concern of philosophers with the problem of maintaining the stability of the state and society. Attention is focused on the fact that there is a need to observe the law of conformity in the recommendations for rulers on how to govern the people.Analysis of the main source of ancient Indian philosophy, which deals with the problems of governance, shows that the recommendations to the king, which are set forth by the author of Arthashastra Kautilya, imply, in the end result, the need to maintain a balance of interests between the ruling class and the people, that is, to observe the measure for which society loses its stability due to for the impoverishment of the people. In other words, in the management recommendations, the law of conformity, which was discussed above, appears in a latent form.Conclusion. The problem of the stability of the social system in a class society was and remains extremely relevant. The philosophical law of correspondence between real relations and the essence of social relations, which ensures the stability of society while observing the measure, requires justification. Since the principle of forming relationships and the nature of interaction has remained unchanged for centuries, the reflections of ancient philosophers on management, on the structure of society, on the relationship between different groups in it, and on the interaction of interests, on the one hand, confirm the operation of this law, on the other hand, could be useful for modern management.